2022
DOI: 10.1038/s41598-022-26144-8
|View full text |Cite
|
Sign up to set email alerts
|

Driving pressure-guided ventilation improves homogeneity in lung gas distribution for gynecological laparoscopy: a randomized controlled trial

Abstract: To investigate whether driving pressure–guided ventilation could contribute to a more homogeneous distribution in the lung for gynecological laparoscopy. Chinese patients were randomized, after pneumoperitoneum, to receive either positive end expiratory pressure (PEEP) of 5 cm H2O (control group), or individualized PEEP producing the lowest driving pressure (titration group). Ventilation homogeneity is quantified as the global inhomogeneity (GI) index based on electrical impedance tomography, with a lower inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Previous studies have confirmed that both incremental and decremental titrations reduce intraoperative shunting; however, only decremental titration improves oxygenation and reduces the airway pressure fluctuations required for pulmonary ventilation 26 . Another recent study suggested that incremental PEEP titration also improves oxygenation 27 and lung gas distribution uniformity in patients undergoing gynecologic laparoscopy 28 . Therefore, patients who underwent OLV during thoracoscopic surgery were included in this study and were studied in conjunction with personalized PEEP titration and PCV‐VG.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have confirmed that both incremental and decremental titrations reduce intraoperative shunting; however, only decremental titration improves oxygenation and reduces the airway pressure fluctuations required for pulmonary ventilation 26 . Another recent study suggested that incremental PEEP titration also improves oxygenation 27 and lung gas distribution uniformity in patients undergoing gynecologic laparoscopy 28 . Therefore, patients who underwent OLV during thoracoscopic surgery were included in this study and were studied in conjunction with personalized PEEP titration and PCV‐VG.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies of prone position surgery have demonstrated that PCV ventilation strategies can reduce the severity of lung injury (5,6). However, the PCV ventilation strategy also has shortcomings; for instance, tidal volume is difficult to control, and it is relatively challenging to judge respiratory mechanical changes (18)(19)(20). During PCV, the preset pressure level is reached at a higher initial inspiratory flow rate at the beginning of the inspiratory process, which decreases exponentially with the inspiratory time until the end of the inspiratory process.…”
Section: Discussionmentioning
confidence: 99%
“…The higher compliance and lower DP obtained strongly suggested minimizing lung functional overdistention and collapse. DP scales the tidal volume dependence of the functional lung size and PEEP, so individualizing the ventilatory settings intraoperatively and achieving an optimum DP adapted to the functional lung size is important [ 31 ]. This study supported the idea that a fixed PEEP is not suitable due to the individual characteristics of the patient and surgery [ 16 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%